2014
DOI: 10.3389/fneur.2014.00233
|View full text |Cite
|
Sign up to set email alerts
|

Central Integration of Canal and Otolith Signals is Abnormal in Vestibular Migraine

Abstract: Vestibular migraine (VM), a common cause of vestibular symptoms within the general population, is a disabling and poorly understood form of dizziness. We sought to examine the underlying pathophysiology of VM with three studies, which involved the central synthesis of canal and otolith cues, and present preliminary results from each of these studies: (1) VM patients appear to have reduced motion perception thresholds when canal and otolith signals are modulated in a co-planar manner during roll tilt; (2) perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 48 publications
1
36
0
1
Order By: Relevance
“…In the past years, in addition to functional changes in patients with migraine, structural abnormalities have been demonstrated in brain areas involved in processing of pain perception and its cognitive-affective contents [18][19][20][21]. However, despite advances in neuroimaging techniques, it is not yet clear if migraine is associated with gray matter (GM) changes [22].…”
Section: Discussionmentioning
confidence: 97%
“…In the past years, in addition to functional changes in patients with migraine, structural abnormalities have been demonstrated in brain areas involved in processing of pain perception and its cognitive-affective contents [18][19][20][21]. However, despite advances in neuroimaging techniques, it is not yet clear if migraine is associated with gray matter (GM) changes [22].…”
Section: Discussionmentioning
confidence: 97%
“…This finding supports the hypothesis that VM does not result from a general increased vestibular sensitivity. Instead, as previously suggested, increased vestibular sensitivity in VM could be a manifestation of abnormal central integration of canal and otolith signals, perhaps at the level of the caudal cerebellar vermis [33]. Other mechanisms such as increased excitability in thalamus [34] or alteration of brain regions characteristic for pain, multisensory vestibular processing and central vestibular compensation [35] in patients suffering VM may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…The present study compared the vestibular function test between the observation group and the control group and showed that the observation group had markedly higher abnormality rates in the caloric test, head‐shaking test, and vestibular autorotation test than the control group, indicating that VM can affect the vestibular peripheral and central functions. The central and peripheral vestibular regions participate in the pathogenic process of VM together, and when the integration of the vestibular and pain signaling pathways is abnormal, the migraine signal at the specific cortex will be integrated by the abnormal region and induces vestibular symptoms …”
Section: Discussionmentioning
confidence: 87%
“…16 All studies above have demonstrated that there is a correlation between 5-HT and the onset of VM, and the decrease in when the integration of the vestibular and pain signaling pathways is abnormal, the migraine signal at the specific cortex will be integrated by the abnormal region and induces vestibular symptoms. [18][19][20] The current studies have suggested that VM, a multigenic disease, is associated with the functional mutations of multiple ion channels and receptors in the vestibular and pain transmission pathways. 5-HRT6 is one of the 5-HT receptors, and its gene, located on chromosome 1p36-p35, can encode the proteins of the G protein-coupled receptor family and is expressed in tissues, such as the frontal cortex, caudate nucleus, and amygdala.…”
Section: Discussionmentioning
confidence: 99%